POST-COVID-19: Persistent symptoms and relationship to the level of fatigue (Research, Society and Development, 2023)
Persistent post-COVID-19 symptoms appear similar to other post-infectious fatigue syndromes, particularly when persistent beyond six months. Therefore, the aim of the study was to evaluate persistent symptoms and their relationship with the level of fatigue, especially above six months post-COVID-19. The individuals were invited by social networks and the questionnaire was made available through an online link using the Google Forms platform. The informed consent was made available on the first page of the form and then the individuals answered the questionnaire on persistent symptoms and level of fatigue using the FACIT-F scale. The Mann Whitney test was used to compare FACIT-F scores between individuals with and without post-COVID-19 symptoms for both the total group and those who continued to have symptoms after 6 months of COVID-19. After data collection, it was observed that the most reported symptoms were: hair loss (43%), forgetfulness/memory loss (30.6%), sweating (23.8%), muscle weakness (21.2% ), dyspnea (20.2%), headache (16.6%), trouble sleeping (15%), confusion or lack of concentration (14%), dry cough (12.4%), pain or swelling in the joints (11.9%), changes in smell and taste (11.9%), persistent muscle pain and palpitations (11.4%). The level of fatigue was higher for those with symptoms. Thus, it is concluded that there was heterogeneity in the prevalence of symptoms, but those with symptoms showed a higher level of fatigue, especially after six months post-COVID-19.